Mini plastic injection moulding / Muhammad Arsyad Nashrol Azam - Muhammad Arsyad, Nashrol Azam (2022)
This is the final year project which is for fabrication and also do the dissertation based on the project title. The project that will be presenting is Design and Fabricate the Mini Plastic Injection Moulding. The used for mini-injection moulding is, it can convert from recycle items such as plastics bottles, polystyrene and also polypropylene which is the raw material to useful items such as plastic paper clips, keychain or plastic comb hair. The project will be discussed about general injection moulding in industry, the heater that been used in injection moulding, plastic that been used in injection moulding and also the steel that been used to build mini-injection moulding. The project also discuss about the mini injection moulding. The conclusion is that the project of mini plastic injection moulding can inject the raw material plastic into a mould and from that it will be a useful item.